A high‐throughput capillary isoelectric focusing immunoassay for fingerprinting protein sialylation. (8th December 2015) - Markely, Lam Raga Anggara; Cheung, Lila; Choi, Young Jun; Ryll, Thomas; Estes, Scott; Prajapati, Shashi; Turyan, Iva; Frenkel, Ruth; Sosic, Zoran; Lambropoulos, James; Tescione, Lia; Ryll, Thomas; et al.
Abstract : The serum half‐life, biological activity, and solubility of many recombinant glycoproteins depend on their sialylation. Monitoring glycoprotein sialylation during cell culture manufacturing is, therefore, critical to ensure product efficacy and safety. Here a high‐throughput method for semi‐quantitative fingerprinting of glycoprotein sialylation using capillary isoelectric focusing immunoassay on NanoPro (Protein Simple) platform was developed. The method was specific, sensitive, precise, and robust. It could analyze 2 μL of crude cell culture samples without protein purification, and could automatically analyze from 8 samples in 4 h to 96 samples in 14 h without analyst supervision. Furthermore, its capability to detect various changes in sialylation fingerprints during cell culture manufacturing process was indispensable to ensure process robustness and consistency. Moreover, the changes in the sialylation fingerprints analyzed by this method showed strong correlations with intact mass analysis using liquid chromatography and mass spectrometry. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 32:235–241, 2016